Evaluasi Pengalaman Pengguna dalam Layanan Buku Pelaut Online: Pendekatan Customer Experience Mapping di KSOP Kelas III Parepare - Razak, Muhammad Rais Rahmat; Prima Adi Laksana; Erfina, Erfina (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Digital transformation in public services is a necessity for realizing an efficient, transparent, and adaptive bureaucracy. One form of such innovation is the Online Seafarer's Book service implemented by the Port Authority and Port Authority (KSOP) Class III Parepare. This study aims to evaluate the quality of this service from the user experience perspective using the Customer Experience Mapping approach. This approach enables a comprehensive mapping of the user journey, from the initial access stage to the completion of the service. The study employs a descriptive qualitative method with data collection techniques including in-depth interviews, observations, and documentation, as well as data analysis using NVivo 14 software. The results indicate that this service has improved administrative efficiency; however, users still face several challenges, such as difficulties in uploading documents, forms experiencing errors, and unstable system responses. Additionally, the clarity of procedural information and the responsiveness of staff are crucial aspects in shaping user satisfaction. This study concludes that the success of public digital services is not only determined by the technical reliability of the system but also by an inclusive and adaptive user experience design. The implications of these findings include the need for system optimization, enhancing human resource capacity in service delivery, and strengthening real-time user feedback mechanisms.